THE FOUNDATIONS OF CONSTRUCTIVIST APPROACH OF PHYSICAL EDUCATION. (Fiep Bulletin - online, 2011)
Abstract: This study aims to examine the foundations of the constructivist approach of physical education. To achieve this goal, a study of the thought of Piaget will be done, since the renowned author is the main source of the assumptions that underlie this approach, which calls for the study of his works for a better understanding of its political and pedagogical implications. From the perspective of dialectical and historical materialism is possible to identify problems in the constructivist approach, which is stuck to the parameters of learner-centered teaching, and therefore inherits the bourgeois visions of man and society advocated by Piaget.
Keywords: Physical Education in school; Piaget; Jean; 1896-1980; Constructivism (Education); Education - Philosophy